Clinical and molecular characteristics and long-term outcomes of pediatric intracranial meningiomas: a comprehensive analysis from a single neurosurgical center - Leihao Ren; Jiaojiao Deng; Hiroaki Wakimoto; Qing Xie; Ye Gong; Lingyang Hua (Acta Neuropathologica Communications)
Abstract Background Meningioma represents the most common intracranial tumor in adults. However, it is rare in pediatric patients. We aimed to demonstrate the clinicopathological characteristics and long-term outcome of pediatric meningiomas (PMs). Method We enrolled 74 patients with intracranial PMs and analyzed their clinicopathological characteristics. Targeted next generation sequencing was used to detect alterations in meningioma relevant genes. Progression-free survival (PFS) was compared between PMs and adult meningiomas (AMs). Univariate and multivariate Cox analyses were employed to evaluate the predictive values of clinicopathological characteristics. A nomogram was constructed and its predictive accuracy evaluated. Result 40 females (54.1%) and 34 males (45.9%) patients, with the gender ratio of 1.18:1, were identified. 9 (12.2%) cases were clinically diagnosed as NF2-related Schwannomatosis (NF2-SWN), while 65 (87.8%) were sporadic. Ventricular location was found in 16 patients (21.6%). 19 patients (25.7%) experienced recurrence during a median follow-up period of 33 months (range 2 -145.25 months). The 3-, 5-, and 8-year PFS rates was 74.74%, 74.74%, and 59.38%, respectively. The PFS of the PM and AM cohorts were not significantly different, with or without propensity score matching. NF2 mutation was observed in 33 sporadic PMs (52.4%), whereas alterations in other genes (AKT1, TRAF7, SMO, PIK3CA, KLF4) frequently mutated in AMs, were not identified. The proportion of NF2 mutation in PMs was significantly lower in the skull base than other locations (p = 0.02). One anaplastic PM harbored TERT promoter mutation. Of note, in sporadic PMs, NF2 mutations were not significantly associated with PFS (p = 0.434) or overall survival (OS) (p = 0.60). The multivariate Cox analysis showed NF2-SWN (p < 0.001) and extent of resection (p = 0.013) to be independently associated with the PFS of PMs. Our prognostic model showed predictive accuracy for long-term PFS in PMs as the 3-, 5- and 8-year Area Under the Curve (AUC) was 0.927, 0.930, and 0.870, respectively. Conclusion PM was characterized by its relative male predominance, ventricular location, NF2-SWN, and NF2 mutation. Of note, PMs had similar prognosis to AMs and NF2 alteration was not significantly associated with PFS in PMs.